New Species of Empidinae (Diptera) from San Rossore National Park, Italy, with the First Report on Leg Polymorphism in the Genus Hilara Meigen and Their DNA Barcoding Evidence - Miroslav Barták; Milan Kozánek; Antonio Belcari; Andrea Š. Tóthová (Insects)
Altogether three species of Empidinae are described from San Rossore National Park, Italy: Empis (Euempis) sanrossorensis Barták sp. nov., Hilara polymorpha Barták sp. nov., and Rhamphomyia (Megacyttarus) sanrossorensis Barták sp. nov. Polymorphism in the shape of foreleg in Hilara is reported for the first time. The COI sequences for barcoding purposes and upcoming studies are provided.